Cyanotype the blueprint in contemporary practice - Anderson, Christina Z (Contemporary practices in alternative process photography series, 2019)
"Cyanotype: The Blueprint in Contemporary Practice is a two part book on the much admired blue print process. Part One is a comprehensive how-to on the cyanotype process for both beginner and advanced practitioners, with lots of photographs and clear, step-by-step directions and formulas. Part Two highlights contemporary artists who are using cyanotype, making work that ranges from the photographic to the abstract, from the traditional to the conceptual, with tips on their personal cyanotype methods alongside their work. These artists illustrate cyanotype’s widespread use in contemporary photography today, probably the most of any alternative process. Book features include: A brief discussion of the practice of the process with some key historical points How to set up the cyanotype ÒdimroomÓ The most extensive discussion of suitable papers to date, with data from 100+ papers Step-by-step digital negative methods for monochrome and duotone negatives Chapters on classic, new, and other cyanotype formulas Toning to create colors from yellow to brown to violet Printing cyanotype over palladium, for those who want to temper cyanotype’s blue nature Printing cyanotype on alternate surfaces such as fabric, glass, and wood More creative practice ideas for cyanotype such as handcoloring and gold leafing Troubleshooting cyanotype, photographically illustrated Finishing, framing, and storing cyanotype Contemporary artists’ advice, techniques, and works Cyanotype is backed with research from 120 books, journals, and magazine articles from 1843 to the present day. It is richly illustrated with 400 photographs from close to 80 artists from 14 countries. It is a guide for the practitioner, from novice to expert, providing inspiration and proof of cyanotype’s original and increasing place in historical and contemporary photography."--